DEVELOPMENT OF E-MANAGEMENT FOR LMS APPLICATION BASED EDUCATION - Wahyuli Lius Zen; Zulvia Trinova (Jurnal Teknik Informatika (Jutif), 2022)
Development of E- School Management using LMS. This research aims to find out: E- Management media development design using Learning Management system (LMS) application, Research Method used in this research is research with development(Research and Development). The development model used in the study was adapted from Borg &Gall. It begins by looking for information from various sources about the problem, needs and solutions to be provided, then continue on planning what about the product that is it will be designed, after which it continues on the initial stage design of lms-based e-management development first made, after which validation is carried out by experts who Consisting of two media experts, once valid then the researcher proceeds at the limited scale test stage Of the research subject in development research. Data analysis used in this study is qualitative analysis with data collection methods using the results of interviews, observations and also discussion results. In this study the results obtained are the development of E-management applications using LMS is very feasible to use with presentation results as much as 78% and very feasible. used.